Advancements in research on the precise eradication of cancer cells through nanophotocatalytic technology - Yao, Changyang; Zhang, Chensong; Fan, Dongwei; Li, Xuanhe; Zhang, Shaofa; Liu, Daoxin (Frontiers in Oncology, 2025)
The rapid development of nanotechnology has significantly advanced the application of nanophotocatalysis in the medical field, particularly for cancer therapy. Traditional cancer treatments, such as chemotherapy and radiotherapy, often cause severe side effects, including damage to healthy tissues and the development of drug resistance. In contrast, nanophotocatalytic therapy offers a promising approach by utilizing nanomaterials that generate reactive oxygen species (ROS) under light activation, allowing for precise tumor targeting and minimizing collateral damage to surrounding tissues. This review systematically explores the latest advancements in highly efficient nanophotocatalysts for cancer treatment, focusing on their toxicological profiles, underlying mechanisms for cancer cell eradication, and potential for clinical application. Recent research shows that nanophotocatalysts, such as TiO2, In2O3, and g–C3N4 composites, along with photocatalysts with high conduction band or high valence band positions, generate ROS under light irradiation, which induces oxidative stress and leads to cancer cell apoptosis or necrosis. These ROS cause cellular damage by interacting with key biological molecules such as DNA, proteins, and lipids, triggering a cascade of biochemical reactions that ultimately result in cancer cell death. Furthermore, strategies such as S–scheme heterojunctions and oxygen vacancies (OVs) have been incorporated to enhance charge separation efficiency and light absorption, resulting in increased ROS generation, which improves photocatalytic performance for cancer cell targeting. Notably, these photocatalysts exhibit low toxicity to healthy cells, making them a safe and effective treatment modality. The review also discusses the challenges associated with photocatalytic cancer therapy, including limitations in light penetration and the need for improved biocompatibility. The findings suggest that nanophotocatalytic technology holds significant potential for precision cancer therapy, paving the way for safer and more effective treatment strategies.